THE INFLUENCE OF PRODUCT KNOWLEDGE AND PRODUCT INVOLVEMENT TOWARD PURCHASE DECISION OF NISSAN CARS CUSTOMERS - Tamboto, Filia C.; Pangemanan, Sifrid S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: This study aims to analyze the influence of product knowledge and product involvement toward purchase decision. Product knowledge and product involvement are expected to lead the customers purchase decision. In partial test, the purpose of this study are: 1) to analyze the influence of product knowledge toward purchase decision, 2) to analyze the influence of product involvement toward purchase decision. The population of this research is Nissan cars customers in Manado. The samples are 100 customers as the respondents. The data was analyzed using multiple regression method. The finding of this study is product knowledge and product involvement have strong and positive correlation with purchase decision. The result of this study indicates product knowledge has significant effect on purchase decision otherwise product involvement has no significant effect on purchase decision. The recommendation for Nissan company is to provide as many as possible of the information about the product in any media and to train the sales person to have all the knowledge about the product.Â Keywords: purchase decision, product knowledge, product involvement